2017
DOI: 10.1002/anie.201706323
|View full text |Cite
|
Sign up to set email alerts
|

Ta(CNDipp)6: An Isocyanide Analogue of Hexacarbonyltantalum(0)

Abstract: Hexakis(2,6-diisopropylphenylisocyanide)tantalum is the first isocyanide analogue of the highly unstable Ta(CO) and represents the only well-defined zerovalent tantalum complex to be prepared by conventional laboratory methods. Two prior examples of homoleptic Ta complexes are known, Ta(benzene) and Ta(dmpe) , dmpe=1,2-bis(dimethylphosphano)ethane, but these have only been accessed via ligand co-condensation with tantalum vapor in a sophisticated metal-atom reactor. Consistent with its 17-electron nature, Ta(C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Attempts to obtain reliable solution magnetic data for 3 by the Evans NMR method were unsuccessful due to its poor solubility in unreactive solvents. However, the paramagnetic nature of 3 was confirmed from its 1 H and 13 C NMR spectra, which show strongly shifted resonances in positions similar to those reported for the closely Multi-scan (SADABS; Sheldrick, 1996) Multi-scan (SADABS; Sheldrick, 1996) Multi related 17-electron V(CNXyl) 6 , which has a magnetic moment consistent with an S = 1 2 spin centered on the V atom (Barybin et al, 2000) and the more recently reported Ta(CNDipp) 6 (Chakarawet et al, 2017).…”
Section: Synthesis and Crystallizationsupporting
confidence: 79%
See 2 more Smart Citations
“…Attempts to obtain reliable solution magnetic data for 3 by the Evans NMR method were unsuccessful due to its poor solubility in unreactive solvents. However, the paramagnetic nature of 3 was confirmed from its 1 H and 13 C NMR spectra, which show strongly shifted resonances in positions similar to those reported for the closely Multi-scan (SADABS; Sheldrick, 1996) Multi-scan (SADABS; Sheldrick, 1996) Multi related 17-electron V(CNXyl) 6 , which has a magnetic moment consistent with an S = 1 2 spin centered on the V atom (Barybin et al, 2000) and the more recently reported Ta(CNDipp) 6 (Chakarawet et al, 2017).…”
Section: Synthesis and Crystallizationsupporting
confidence: 79%
“…In contrast to 2, 3 is a mononuclear complex containing six equivalent and discrete isocyanide ligands (Fig. 4), wherein the Nb(CN) 6 core structure is best described as a slightly distorted octahedron very similar to that present in the recently reported tantalum analog Ta(CNDipp) 6 (Chakarawet et al, 2017). The Nb-C distance of 2.1542 (15) Å in 3 (Table 3) is slightly longer than the Ta-C distance of 2.135 (1) Å in Ta(CNDipp) 6 .…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…However, from this bulk sample the original single crystals of the desired compound for X-ray crystallography were obtained as follows: a concentrated solution of the solid in THF was layered with pentane at 250 K and, after several days, deep-red nearly black parallelepipeds were harvested. Later, pure bulk samples of TaI(CNDipp) 6 were prepared by a similar procedure, but it was necessary to heat the reaction mixture to about 338 K, just above the normal boiling point of THF, for 20 h for quantitative displacement of carbon monoxide (Chakarawet et al, 2017).…”
Section: Synthesis and Crystallizationmentioning
confidence: 99%
“…[Mn(CO) 6 ][Mn(CO) 5 ] or [Co(CO) 5 ][Co(CO) 4 ], are unknown and appear to be intrinsically unstable to comproportionation (Lee & Kochi, 1989;Kochi & Bockman, 1991). Indeed, in a recent study, it was shown that addition of equimolar amounts of the independently prepared and isolated [Ta(CNDipp) 7 ]BF 4 to K[Ta(CNDipp) 6 ] in tetrahydrofuran (THF) at 273 K afforded only the monomeric 17electron Ta 0 complex Ta(CNDipp) 6 , along with KBF 4 , and free CNDipp (Chakarawet et al, 2017). On this basis and other information (see below), it is concluded that salt 2 only exists in the solid state.…”
Section: Introductionmentioning
confidence: 99%